(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
According to the Philippines Department of Trade and Industry (DTI), a start-up is defined as “innovating products and creating new business models that address changing societal and market needs." The core of the Philippine economy is comprised of small companies. They encourage economic progress, foster innovation, and produce jobs. The study utilized a mixed-method research design in which participants of the study were ten (10) customers of Garahe ni Kuya Jo and thirty (30) customers of new start-up local businesses around Garahe ni Kuya Jo along Novaliches, Quezon City. In order to interpret the data gathered, statistical tools such as frequency, percentage, weighted mean, and rating scale were used. From the result of the study, the assessment on the utilization of marketing mix in terms of product, price, place, promotion, and people overall: Pap’s Buffalo Chicken, Food Hub Kalye Susano Est. 2022, and Garahe ni Kuya Jo strongly agree. Also, Paper Bucket agreed.; with the assessment on the impact of the marketing mix on the new start-up local businesses around Garahe ni Kuya Jo in terms of brand image, ambiance, food presentation, cleanliness, and taste overall: the Pap’s Buffalo Chicken, Food Hub Kalye Susano Est. 2022, and Garahe ni Kuya Jo got strongly agree. Also, Paper Bucket was agreed upon. There is a statistically significant difference among these local businesses around Garahe ni Kuya Jo with the treatment Pap’s Buffalo Chicken, Paper Bucket, and Kalye Susano Food Hub Est. 2022, contributing significantly to the variation observed. There is a highly significant and positive relationship between the marketing mix and its impact on new start-up local businesses, implying that how the marketing mix is managed has a substantial effect on these businesses. This study recommended that management should be required to make sure that their employees are properly trained to carry out their jobs in accordance with the rules and regulations in order to maintain the safety of the business and their customers. Also, the new local start-up businesses should be able to expand the area they serve based on recommendations. Always make sure to provide the customer with a safe parking area. Providing suitable bathrooms and maintaining them. Lastly, businesses should implement guidelines to enhance the quality of their services and products to maintain their customers.